2018
DOI: 10.1123/japa.2016-0363
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of Attendance and Adherence to Group-Based Physical Activity for Older Adults: A Literature Synthesis

Abstract: This review examines program features that influence attendance and adherence to group-based physical activity (PA) by older adults. Medline, PubMed, CINAHL plus, PsycINFO, and the Cochrane Library were searched for studies published from 1995-2016. Quantitative and qualitative studies investigating factors related to PA group attendance or adherence by persons aged 55 years and over were included. Searching yielded eight quantitative and 13 qualitative studies, from 2,044 titles. Quantitative findings identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…The intensity of an exercise programme is an important factor for determining the physiological stress and subsequent adaption an individual can experience through training. If the frequency and intensity of the training programme is too high, muscular damage may occur and this can negatively affect adherence to programmes [64]. The Borg Scale is a valid and simple measure of controlling intensity that has been utilised within the studies analysed [16, 26, 27, 29, 30, 34, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of an exercise programme is an important factor for determining the physiological stress and subsequent adaption an individual can experience through training. If the frequency and intensity of the training programme is too high, muscular damage may occur and this can negatively affect adherence to programmes [64]. The Borg Scale is a valid and simple measure of controlling intensity that has been utilised within the studies analysed [16, 26, 27, 29, 30, 34, 36].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Fennell et al [43] found a significant increases in level of physical activity and muscular endurance when training intervention was supervised by exercise professionals; however, when receiving only recommendations for the practice of physical activity without supervision, the participants returned to baseline scores, losing the acquired effects. Probably these results can be explained by motivational factors [44,45]. In this context, it was demonstrated that high level of satisfaction can be reached in activities that are more pleasant cause highest levels of life satisfaction [46].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the first telephone calls were mainly used to form the relationship between the counsellor and the participant and rarely for actual MI-content. Secondly, the participants included in this trial were mainly well-educated, active and resourceful older adults with high levels of health literacy, which might affect the generalizability to the background population of older adults, as previous research has shown that exercise and physical activity adherence are associated with resources such as social support and the ability to understand the benefits of physical activity [ 74 76 ].…”
Section: Discussionmentioning
confidence: 99%